2016
DOI: 10.1016/j.jval.2016.03.1537
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Disease Outcomes in Symptomatic Multiple Myeloma Patients: A Retrospective Analysis of the Pharos Registry

Abstract: Objectives: Leading medical professional societies (eg, ASCO, ESMO, NCCN) have recently released frameworks to facilitate discussions on the value of cancer therapies. This literature review summarizes recent trends on the concept of evaluating value in cancer care, using mCRC as an example. MethOds: Relevant publications were identified using predetermined search criteria in Medline (01/01/2005-12/31/2015) and abstracts presented at key conferences (01/01/2015-12/31/2015). Publications were reviewed if they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
6
3
0
Order By: Relevance
“…PFS probabilities for the overall cohort and older patients appeared to decrease sharply between patients receiving their second and third LOTs, in support of previous real-world European data (Yong et al, 2016). Median PFS for younger patients in our study receiving their first and second LOTs were 39 months and 9 months, respectively, compared to 23 months and 9 months, as previously reported in patients of similar age (≤65 years) enrolled in a Dutch registry (Verelst et al, 2016). Median PFS in older patients receiving their first and second LOT were 15 and 7 months, which were similar to the 16 and 9 months reported from the Dutch registry in their older cohort of patients, above 66 years (Verelst et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…PFS probabilities for the overall cohort and older patients appeared to decrease sharply between patients receiving their second and third LOTs, in support of previous real-world European data (Yong et al, 2016). Median PFS for younger patients in our study receiving their first and second LOTs were 39 months and 9 months, respectively, compared to 23 months and 9 months, as previously reported in patients of similar age (≤65 years) enrolled in a Dutch registry (Verelst et al, 2016). Median PFS in older patients receiving their first and second LOT were 15 and 7 months, which were similar to the 16 and 9 months reported from the Dutch registry in their older cohort of patients, above 66 years (Verelst et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…PFS probabilities at 12 and 24 months for our overall cohort receiving their first LOT appears to be broadly in line with the ~60%–70% and 40%–50% reported by the Dutch registry (Verelst et al, ) and a French registry study (Mounier et al, ). It is possible that any differences between our study and the Dutch and French registry data may be due to differences in the date of study enrolment—2004 in Verelst et al, 2008 in Mounier et al, relative to 2012 in our study (Verelst et al, ), which therefore reflect a difference in the available treatment armamentarium. According to data from a real‐world population in the United States, there does appear to be a survival disparity based on date of diagnosis for patients with multiple myeloma (Fonseca et al, ), which may explain some of the disparities observed.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations